Find the value of x, if sin x, sin 2x, sin 3x are in A.P
A) $n\pi ,{\text{ }}n \in l$
B) $nx,{\text{ }}n \in l$
C) $2n\pi ,{\text{ }}n \in l$
D) $\left( {2n + 1} \right)\pi ,{\text{ }}n \in l$
Answer
Verified
510.3k+ views
Hint: First use the property of arithmetic progression to the given terms and obtain an equation using trigonometric identities. Solve them using trigonometric equation solutions.
Complete step-by-step answer:
Given that $\sin x$, $\sin 2x$, $\sin 3x$ are in arithmetic progression.
We know that if a,b and c are in arithmetic progression, then the successive terms have equal difference, that is,
$2{\text{b = a + c}}$
Using the above relation in the given problem, we get
$2\sin 2x = \sin x + \sin 3x{\text{ ---- (1)}}$
We know from trigonometric sum to product formula that
$\sin x + \sin y = 2\sin \left( {\dfrac{{x + y}}{2}} \right)\cos \left( {\dfrac{{x - y}}{2}} \right)$
Using the above formula in the RHS of equation $(1)$, we get,
$
2\sin 2x = \sin 3x + \sin x = 2\sin \left( {\dfrac{{3x + x}}{2}} \right)\cos \left( {\dfrac{{3x - x}}{2}} \right) \\
\Rightarrow 2\sin 2x = 2\sin \left( {2x} \right)\cos \left( x \right) \\
$
Rearranging the above obtained equation, we get
$2\sin \left( {2x} \right)\left( {1 - \cos x} \right) = 0$
$ \Rightarrow \sin \left( {2x} \right) = 0{\text{ ---- (2)}}$
Or $\left( {1 - \cos x} \right) = 0{\text{ ---- (3)}}$
Now we need to solve equations $(2)$ and $(3)$ and then obtain the common solution.
We know that the general solution of $\sin z = 0$ is $z = n\pi {\text{ , }}n \in l$ ,where $l$ denotes integers.
Using above in equation $(2)$,we get,
$
\sin \left( {2x} \right) = 0{\text{ }} \Rightarrow 2x = n\pi \\
\Rightarrow x = \dfrac{{n\pi }}{2}{\text{, }}n \in l{\text{ ---- (4)}} \\
$
Similarly, we know that the general solution of $\cos z = 1$ is $z = 2n\pi {\text{ , }}n \in l$,where $l$ denotes integers.
Using above in equation $(3)$,we get,
$
\cos \left( x \right) = 1{\text{ }} \Rightarrow x = 2n\pi \\
\Rightarrow x = 2n\pi ,n \in l{\text{ ---- (5)}} \\
$
The intersection of solutions $(4)$and $(5)$ is $x = 2n\pi {\text{, }}n \in l$, which satisfies both the equations.
Hence (C). $x = 2n\pi {\text{, }}n \in l$ is the correct answer.
Note: Properties of arithmetic progression and solutions of the trigonometric equations should be kept in mind while solving problems like above. The intersection of solutions should always be verified with the original equations.
Complete step-by-step answer:
Given that $\sin x$, $\sin 2x$, $\sin 3x$ are in arithmetic progression.
We know that if a,b and c are in arithmetic progression, then the successive terms have equal difference, that is,
$2{\text{b = a + c}}$
Using the above relation in the given problem, we get
$2\sin 2x = \sin x + \sin 3x{\text{ ---- (1)}}$
We know from trigonometric sum to product formula that
$\sin x + \sin y = 2\sin \left( {\dfrac{{x + y}}{2}} \right)\cos \left( {\dfrac{{x - y}}{2}} \right)$
Using the above formula in the RHS of equation $(1)$, we get,
$
2\sin 2x = \sin 3x + \sin x = 2\sin \left( {\dfrac{{3x + x}}{2}} \right)\cos \left( {\dfrac{{3x - x}}{2}} \right) \\
\Rightarrow 2\sin 2x = 2\sin \left( {2x} \right)\cos \left( x \right) \\
$
Rearranging the above obtained equation, we get
$2\sin \left( {2x} \right)\left( {1 - \cos x} \right) = 0$
$ \Rightarrow \sin \left( {2x} \right) = 0{\text{ ---- (2)}}$
Or $\left( {1 - \cos x} \right) = 0{\text{ ---- (3)}}$
Now we need to solve equations $(2)$ and $(3)$ and then obtain the common solution.
We know that the general solution of $\sin z = 0$ is $z = n\pi {\text{ , }}n \in l$ ,where $l$ denotes integers.
Using above in equation $(2)$,we get,
$
\sin \left( {2x} \right) = 0{\text{ }} \Rightarrow 2x = n\pi \\
\Rightarrow x = \dfrac{{n\pi }}{2}{\text{, }}n \in l{\text{ ---- (4)}} \\
$
Similarly, we know that the general solution of $\cos z = 1$ is $z = 2n\pi {\text{ , }}n \in l$,where $l$ denotes integers.
Using above in equation $(3)$,we get,
$
\cos \left( x \right) = 1{\text{ }} \Rightarrow x = 2n\pi \\
\Rightarrow x = 2n\pi ,n \in l{\text{ ---- (5)}} \\
$
The intersection of solutions $(4)$and $(5)$ is $x = 2n\pi {\text{, }}n \in l$, which satisfies both the equations.
Hence (C). $x = 2n\pi {\text{, }}n \in l$ is the correct answer.
Note: Properties of arithmetic progression and solutions of the trigonometric equations should be kept in mind while solving problems like above. The intersection of solutions should always be verified with the original equations.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE